Towards large-scale prediction of Lolium rigidum emergence. II. Correlation between dormancy and herbicide resistance levels suggests an impact of cropping systems - Owen, M.; Michael, Pippa; Renton, M.; Steadman, K.; Powles, S. (Blackwell Scientific Publications, 2011)
This study investigated a possible link between seed dormancy and herbicide resistance status of Lolium rigidum (annual or rigid ryegrass). Mature seeds were collected from 406 populations across the 14-million hectare grain belt of southern Western Australia. For each population, initial dormancy and change in dormancy over a 6-month period were measured, and resistance status of seedlings to four herbicides (diclofop-methyl, sethoxydim, clethodim and sulfometuron-methyl) was assessed. Greater seed dormancy correlated with higher levels of herbicide resistance for all four herbicides tested. The herbicides represented two modes of action (acetyl CoA carboxylase- and acetolactate synthase inhibitors) and a contrast of generalist (metabolic) and target-site mutation mechanisms. The coexistence of dormancy and herbicide resistance is suggested to be an adaptation to decades of intense cropping; the plants that are most likely to successfully reproduce are those that exhibit delayed germination (avoiding pre-seeding weed control strategies) and possess herbicide resistance (surviving subsequent in-crop herbicide application). We propose that herbicide resistance status may have a role as a predictive tool in modelling dormancy in L. rigidum at a large spatial scale.